ANALISA FAKTOR YANG MEMPENGARUHI PERILAKU BRANDSWITCHING PRODUK AQUA GALON DI SURAKARTA - muhammad khoiruman (STIE AUB Surakarta, 2016)
The importance of maintaining customer loyalty to keep terjada not brandswitching consumers to other products is the basis of this study. This study aims to determine the effect of variables forming customer loyalty to the consumer brandswitching aqua in Surakarta. This research is a survey with a sample of the overall amount to 250 respondents. The sampling technique used was purposive sampling. Data collection instruments such as questionnaires and analysis tools used multiple linear regression. Based on the results of this study concluded that the dimensions of forming consumer loyalty (post-consumer dissatisfaction, the need to find variations, prices of Aqua, attraction competitors) influence on consumer loyalty and consumer brandswitching aqua in Surakarta. Variable appeal of competitors has the largest and most significant influence on customer loyalty while consumer loyalty variables have the greatest influence and significant impact on consumer brandswitching Aqua gallon in Surakarta Keywords: post-consumer dissatisfaction, the need to find variations, prices of Aqua, attraction competitors, customer loyalty and brandswitching.